Isotretinoin-LIDOSE: 15 years of experience in acne therapy. A review - Luiza R. Sakaniya; Evgeniya V. Dvoriankova; Zofia A. Niewozinska; Ksenia V. Badlueva; Ekaterina S. Andrienko; Tamara V. Beley; Irina M. Korsunskaya (Consilium Medicum)
Isotretinoin is a systemic retinoid and a vitamin A derivative. Since the 1980s, it has established itself as a highly effective treatment for severe acne. The drug acts on several pathogenesis links, reduces the size of the sebaceous glands and sebum production, and has an anti-inflammatory and immunomodulatory effect. The dosing regimen may vary, but multiple studies have shown that the best effect is achieved with 0.5–1 mg/kg daily up to a cumulative dose of 120–150 mg/kg per course. The duration of therapy is usually 8–12 months. For 15 years now, we have been using isotretinoin, manufactured using LIDOSE technology (Aknekutan), to treat moderate to severe acne. LIDOSE technology is a significant improvement of the drug, which made it possible to increase its bioavailability and reduce the food effect, which increased the compliance of therapy and reduced the number of relapses. The author’s observations showed that relapses occur several months after the end of the isotretinoin treatment course. Risk groups include patients with a history of gynecological diseases and surgical interventions. It is important to note that the disease has less pronounced clinical manifestations in case of relapse. To minimize the risk of exacerbation, women are recommended to take oral contraceptives in combination with isotretinoin after completing the course of therapy. Topical therapy is usually sufficient for patients after surgery; only in 3% of cases, a short course of isotretinoin may be required. It should be mentioned that isotretinoin therapy may be associated with side effects like dry skin and mucous membranes and, in some cases, a change in liver function tests. However, these side effects are successfully treated with moisturizers and hepatoprotectors, respectively.